Planning Of Highquality Concrete Mixtures With Additional Superplasticizer And The Effect Of Partial Cement Replacement With Fly Ash - Fandhi Hernando (Sean Institute, 2022)
Various studies and experiments in the field of concrete were carried out as an effort to improve the quality of concrete, material technology and implementation techniques obtained from the results of these studies and experiments were intended to answer the increasingly high demands on the use of concrete and overcome the obstacles that often occur in the implementation of the work. in the field. One way to increase the strength of concrete is to increase its compaction, which is to minimize the pores or cavities that form in the concrete. The use of admixtures can help solve these problems. The purpose of this study was to obtain the compressive strength of high-strength concrete and to determine the effect of the replacement of fly ash and the addition of a superplasticizer on the compressive strength of concrete. The composition of the Supeplasticizer mixture used in this study was 0.6% for all variations and the replacement of fly ash was 0%, 20%, 25%, 30% and 35% of the cement weight. The test object used was cylindrical in shape, the planned concrete quality was 65 MPa which was tested at the age of 28 days with treatment prior to testing. This study tested concrete with cylindrical specimens for compression test (diameter 150 mm and height 300 mm) as many as 50 samples and consisted of 5 variations and each variation was 10 samples. From the research, it was found that the highest compressive strength of concrete was found in the 20% Fly Ash replacement concrete mixture, which was 59.095 MPa and the lowest concrete compressive strength was found in the 30% Fly Ash replacement concrete mixture, which was 42.927 MPa. That with the replacement of 20% Fly Ash has a higher compressive strength compared to other Fly Ash mixed concrete variations. Mixture with a high degree of workability has a great risk of bleeding, this occurs in all concrete samples.